The problem of definition of the object of state control in the sphere of legal turnover of narcotic drugs in Ukraine. - Шевчук, О. М. (Theory and practice of jurisprudence, 2016)
The article is devoted to the issues, associated with the definition of an object of state control in the sphere of legal turnover of narcotic drugs, psychotropic substances and precursors in Ukraine. The notions of and defined the object, the subject of state control in the sphere of legal turnover of narcotic drugs, psychotropic substances and precursor